Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41467-017-00674-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Foxo1 is essential for IL-9 induction in T helper cells

Abstract: Interleukin 9 (IL-9)-producing helper T (Th9) cells have a crucial function in allergic inflammation, autoimmunity, immunity to extracellular pathogens and anti-tumor immune responses. In addition to Th9, Th2, Th17 and Foxp3+ regulatory T (Treg) cells produce IL-9. A transcription factor that is critical for IL-9 induction in Th2, Th9 and Th17 cells has not been identified. Here we show that the forkhead family transcription factor Foxo1 is required for IL-9 induction in Th9 and Th17 cells. We further show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 63 publications
3
100
0
Order By: Relevance
“…Pro‐asthmatic M2 macrophage phenotypes are mainly arbitrated through specific IRF4 transcription factor pathway; therefore, FoxO1 could regulate a key checkpoint of the IRF4 pathway in macrophages. Our data are consistent with this literature that FoxO1 regulates the macrophage inflammatory phenotype through an IRF4‐dependent manner in allergic inflammation and in asthma biology . Mechanistically, FoxO1 is known to bind to IRF4 promoter and mediate transactivation .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Pro‐asthmatic M2 macrophage phenotypes are mainly arbitrated through specific IRF4 transcription factor pathway; therefore, FoxO1 could regulate a key checkpoint of the IRF4 pathway in macrophages. Our data are consistent with this literature that FoxO1 regulates the macrophage inflammatory phenotype through an IRF4‐dependent manner in allergic inflammation and in asthma biology . Mechanistically, FoxO1 is known to bind to IRF4 promoter and mediate transactivation .…”
Section: Discussionsupporting
confidence: 93%
“…Limitation to the current study includes the relatively small number of human samples; however, our results are consistent with the expression of FoxO1 in macrophages that is required for the pro‐asthmatic phenotype which contributes to aggravating the inflammatory reaction of DRA‐induced allergic asthma. Very recent reports have also demonstrated a crucial role of FoxO1 in other type of asthmatic inflammation . Our data, in combination with the literature, suggest that the impact of FoxO1 on the macrophage inflammatory phenotype is transduced through expression of the binding partner, IRF4.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Other transcriptional activators, which have been described to bind to the IL9 promoter and were found to be overexpressed with age, include HIF1α, GATA3, and ETV5 (Kaplan, ; Malik et al, ; Singh, Garden, Lang, & Cobb, ; Wang et al, ). In contrast, BCL6 and ID3, transcriptional repressors of IL9, declined with age.…”
Section: Discussionmentioning
confidence: 99%
“…31,47 IL-5 and IL-9 were recognized to be Th2-associated cytokines and involved in inflammation regulation. 48,49 It was worth noting that the expression of IL-4 in NT-30 is lower than that of P and NT-100 at 3 days. In another study conducted by our group, we found that there were more mast cell infiltrations around the P and NT-100 groups within 3 days after implantation (data not shown).…”
mentioning
confidence: 99%